Two-Dimensional Ethnicity: ISBN 978-606-95069-5-0 - Baghdadi, Parsa (Technium Books, 2021)
A Study of the Misguided Man in Modernism , Finding a Savior in Reaching the Utopia in society of the celebrities and celebrityism The choice of the celebrity[ism ] phenomenon is as a fixed function merely a symbolic study to provide an overview of several abstracts and homogeneous concepts from different views in individual and collective daily life in a creature that according to scientific studies, is the most complex cosmic phenomenon known to date. Because his brain has ability to make non-instinctive choices, it is able to transmit experiences in the form of "dialectically and generationally classified information" and at the same time senses metamorphosis from within as a creature of ugliness and staff. He can also becomes self-aware and engineers his future. Man is a coercived social being, so in his daily encounters and contacts, he experiences many actions-reactions, and this is what determines his behavior and destiny. In the perception of the mass of people, "a celebrity " like other products of "modernity and modernism" is considered as a purely negative thing, and the pathology of this phenomenon needs to be examined more deeply in the human mind [good or evil].Since critical and radical thinking has been one of the main philosophical foundations of Eastern and Western thinkers since World War II, we must be aware that what will brings us to a common conclusion is an approach agreement among thousands of scattered yet close views. Together they aim to reach a common approach at the local and global levels, and also three issues can not be ignored. Youtube video link: https://youtu.be/OXJtvAgpjTk Technium Books publish all content in open access, promoting the exchange of ideas and knowledge in a globalized world. Technium Books encompasses all the benefits of open access—high availability and visibility, as well as wide and rapid dissemination. Technium Books are distributed under the terms and conditions of the Creative Commons Attribution License — as an author, you retain the copyright for your work. Technium Books believes that the contemporary wave in academia of wider and faster dissemination of knowledge with open access should not be restricted to academic journals but should also capture and elevate academic & research book publishing. See visitor map: https://clustrmaps.com/site/1bg5q